Washington Internships : How to Get Them and Use Them to Launch Your Public Policy Career - Martínez, Deirdre (Book collections on Project MUSE., 2009)
For students interested in a career in politics and public service, Washington Internships is an indispensable guide to landing that crucial first position in the internship capital of the United States and being a successful intern.